2017
DOI: 10.4194/1303-2712-v17_5_15
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: This study evaluated the effects of diet containing 1 and 2 g kg -1 T. terrestris extract on growth and reproductive performance of male Convict cichlid (C. nigrofasciatum). 117 male C. nigrofasciatum with an average initial weight of 2.30 ± 0.04 g were distributed into glass aquariums (13 fish/tank) in 3 replicates. The highest weight gain was obtained in 1 g kg -1 (123.83 ± 6.41 g) followed by 2 g kg -1 extract (121.13 ± 8.09 g) and control (80.10 ± 11.71 g) group (P< 0.05). In groups that received extract, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 12 publications
2
3
0
Order By: Relevance
“…The results of present study showed that tribulus terrestris extract has a great positive effect on growth performance, due to androgenic effect of Tribulus terrestris that have a major role in the growth and differentiation of reproductive organs. Similar findings were recorded by Yeganeh et al, (2017) who found that the supplemented T. terrestris extract as a feed additive for C. nigrofasciatum improves growth performance and hatchability per cent. Furthermore, T. terrestris administration increased appetite, food utilization and protein synthesis due to its androgenic effect (Donaldson, 1979;Jayaprakas & Sindhu, 1996;Mukhopadhyay, Venkatesh, & Das, 1986).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The results of present study showed that tribulus terrestris extract has a great positive effect on growth performance, due to androgenic effect of Tribulus terrestris that have a major role in the growth and differentiation of reproductive organs. Similar findings were recorded by Yeganeh et al, (2017) who found that the supplemented T. terrestris extract as a feed additive for C. nigrofasciatum improves growth performance and hatchability per cent. Furthermore, T. terrestris administration increased appetite, food utilization and protein synthesis due to its androgenic effect (Donaldson, 1979;Jayaprakas & Sindhu, 1996;Mukhopadhyay, Venkatesh, & Das, 1986).…”
Section: Discussionsupporting
confidence: 88%
“…In order to reduce the use of antibiotics and other chemicals in the field of aquaculture, many feed additives were used as probiotics and phytobiotics (Elsabagh et al, 2018;Yeganeh, Sotoudeh, & Movaffagh, 2017). Recently, phytobiotics (plant additives) are extensively used as aquafeed additives due to its comparatively harmless natural components and to improve fish growth performance, weight gain and feed conversion ratio in the fish farms (Yeganeh et al, 2017).…”
mentioning
confidence: 99%
“…On the contrary of nursery stage, T9 gave the highest weight gain, final weight, SGR, and best FCR, followed by T8, while the basal diet was the worst. These results may agree with Yeganeh et al (2017) in the superiority of the two doses of T. terrestris extract compared to the control diet, no significant differences were observed among doses of T. terrestris extract in FCR and survival. At the same time, they may differ in that the best effect came with the lowest dose (the highest WG and FW were obtained at 1g/kg -1 followed by 2 g/kg -1 T. terrestris extract).…”
Section: Tribulus Terrestrissupporting
confidence: 87%
“…Hormonal function has been demonstrated by several bioactive chemicals that have been separated from plants. The most active phytoestrogens have estrogenic activity and interact with oestrogen receptors, whereas interactions between isoflavones and phytoestrogens and the androgen and progesterone receptors are less prevalent [42,43]. Earlier studies have shown that plant compounds can mimic sex hormones as agonists or antagonists to nuclear receptors, as well as modulate the biosynthesis of sex hormones by altering the activity and expression of enzymes [44][45][46][47].…”
Section: Discussionmentioning
confidence: 99%